What criteria guide national entrepreneurs’ policy decisions on user fee removal for maternal health care services?: use of a best-worst scaling choice experiment in West Africa: - Torbica, Aleksandra; De Allegri, Manuela; Belemsaga, Danielle; Medina-Lara, Antonieta; Ridde, Valery (Journal of health services research & policy, 2014)
Objective Several countries in sub-Saharan Africa have implemented policies to remove or reduce user fees. Our aim was to identify criteria guiding such decisions among national policy entrepreneurs, those who link up problem definition,solution development and political processes.